Indonesia Teacher Certification and Beyond : An Empirical Evaluation of the Teacher Certification Program and Education Quality Improvements in Indonesia - World Bank (World Bank, Jakarta, 2016)
The certification program aimed to certify all teachers by 2015. The program was rolled out at a rate of approximately 200,000 teachers each year. This report evaluates the certification program as it was implemented, in terms of its impact on student-learning outcomes. Results of the analysis are sobering: despite its massive fiscal implications, the certification program has not led to substantial improvements in student-learning outcomes so far. The report provides leads into how to gradually transform the system into one that can yield higher returns in educational performance going forward. It emphasizes the importance of a system that rewards useful demonstrated competencies, such as minimum levels of subject-matter knowledge, rather than loose proxies for quality such as bachelor’s degrees or seniority alone (which is essentially what the current certification program does). The report also highlights the need for reforms in the pre-service system of teacher training and teacher hiring. Chapter one gives decade on for teacher certification in Indonesia; chapter two presents an empirical review of the teacher certification program in Indonesia; chapter three presents beyond certification: what matters and what doesn’t matter for student learning?; and chapter four presents policy options for sizable and lasting changes in education quality.